CITRA DAN KOMUNIKASI WANITA PEROKOK DI JAKARTA - Arleen Ariestyani (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2019)
The phenomenon of smokers in Indonesia continues to increase and is worrying. In 2017 there are 6.3 million active smokers. During the last fve years female smokers increased by 400 percent and were the highest achievement in the world, including in Indonesia, and most women smokers were of productive age, ie 13 years to 40 years. For women who smoke they have symbols that contain meaning. Symbols are used to communicate between those who unwittingly cause rules in fellow smokers so that they can be understood when communicating. This study aims to determine the relationship between Image and Communication in women smokers in Jakarta and to identify the motives of women smokers in Jakarta. This study uses a qualitative approach in data collection, with the type of research in the form of case studies. Interviews were used to obtain knowledge about relationships resulting from the Image and Communication of Women smokers and the motives of women smokers. The research criteria determined were active smokers, smoking more than 5 years, productive age, in the city of Jakarta. Many of the smokers still think of several things such as Indonesian culture which is still a bit taboo for women smoking and a lot of community assessments about women smoking themselves. In the communication side of women smokers have 2 parts of the category how they interact with others, they share friendships with other people based on the person smoking or not smoking, this is to respect people who do not like smoking.